Evaluate I = ∫ 0 1 x 6 1 − x 2 d x
to 4 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I substituted x = sin u (as 0 ≤ x ≤ 1 )to get ∫ 0 1 s i n 6 ( u ) c o s ( u ) d u = 7 1 [ s i n 7 u ] 0 1 but I didn't get the correct answer. Where did I go wrong?
Log in to reply
because you have forgotten to substitute the d(x) as d(sinu), which is cosu d(u), and the limits would become 0 to pi/2
Clearly I = 2 1 β ( 2 7 , 2 3 ) Where β ( m , n ) is called β function Also by using the properties of β function we can write it in forms of Γ function as I = 2 1 Γ ( 2 7 + 2 3 ) Γ ( 2 7 ) Γ ( 2 3 ) Hence I = 4 × 3 × 2 × 1 2 5 × 2 3 × 2 1 × π × 2 1 × π After solving we get I = 2 5 6 5 π = 0 . 0 6 1 3
There is another method of solving this question i.e using WALLI's Formula
Log in to reply
You should post it here.
Log in to reply
Okay Done it......!!
Log in to reply
@Deepanshu Gupta – Yes I know that x = cos θ Then that ∫ sin m θ cos n θ direct formula to put 'm and n'
Abhishek Singh It is better if you state that the answer must be in four decimal places because 2 5 6 5 π = 0 . 0 6 1 3 5 9 2 3 1 5 1 5 4 2 5 6 … . My answer is wrong because I type 0 . 0 6
Well to see the first part "clearly" we need to make the substitution x 2 ↦ x then it becomes apparent.
Use beta function by taking x^2=u
a long and extended version that i used is by substituting x = s i n θ then applying the property f ( x ) = f ( a + b − x ) finally adding the two integrals as 2 I = ∫ 0 2 π ( s i n θ ) 2 ( c o s θ ) 2 ( ( s i n θ ) 4 + ( c o s θ ) 4 ) d θ
after some simplification i got 2 I = ∫ 0 2 π 4 ( s i n 2 θ ) 2 − 8 ( s i n 2 θ ) 4 d θ
hence after a long integration we finally get the answer 2 5 6 5 π
this is only calculus approached solution !!
After substituting x=sin(theta), you can directly evaluate the integral using Walli's formula.
My solution was closer to yours. By substituting x = cos θ , I reduced the integral to 1 6 1 ∫ 0 2 π sin 2 θ ( 1 + cos 2 θ ) 2 d θ and solved it from there on.
Problem Loading...
Note Loading...
Set Loading...
Wallis Theorem states that :
∫ 0 2 π sin m θ cos n θ d θ = k ( ( m + n ) ( m + n − 2 ) ( m + n − 4 ) . . . . . . . . . . . . . . . . . . 1 o r 2 ) ( ( m − 1 ) ( m − 3 ) ( m − 5 ) . . . . . . . . . . . 1 o r 2 ) ( ( n − 1 ) ( n − 3 ) ( n − 5 ) . . . . . . . . . . . 1 o r 2 ) w h e r e m , n a r e w h o l e n u m b e r s K = 2 π i f m & n b o t h a r e e v e n . = 1 O t h e r w i s e . .
Let's Back to the Question
Put x = sin θ .
d x = cos θ d θ
So given Integral becomes:
I = ∫ 0 2 π sin 6 θ cos 2 θ d θ .
By using Wallis Formula ( m=6 & n=2 )
I = ∫ 0 2 π sin 6 θ cos 2 θ d θ = 2 π ( 8 . 6 . 4 . 2 ) ( 5 . 3 . 1 ) ( 1 ) = 2 5 6 5 π .